Evaluating Affecting Factors on Sexual Function of Menopausal Women - Zeinab Bayat; Samaneh Youseflu; Majid Yousefi Afrashteh; Soudabeh Niroomand (Preventive Care in Nursing and Midwifery Journal, 2021)
Background: Sexual problems are very prevalent in climacteric periods due to hormonal, social, and physiological changes, and sexual dysfunction of women can affect women’s self-confidence, marital relationship, and quality of life. Objectives: This study was done to investigate the relationship between urinary incontinence, vaginal dryness, prolapse, hot flush, and education with the sexual function of menopause women. Methods: This cross-sectional study was done on 408 women who were referred to health care centers in Zanjan, Iran between 2018 and 2019. Sampling was performed using a systematic randomized sampling method. Data collection tools were a checklist consists of questions about socio-demographic and reproductive information and the 19-item Female Sexual Function Index (FSFI) questionnaire. All data were analyzed using SPSS version 16 through regression analysis and a P-value<0.05 was considered significant. Results: The mean age of women was 47.90±3.57 years. This study found the relationship between sexual function score and urinary incontinence (β=0.18, t=3.70, p<0.001), vaginal dryness (β=0.27, t=5.73, p<0.001), prolapse (β=-0.14, t=-2.97, p<0.001), and hot flush (β=0.16, t=3.35, p<0.001); however, there was no relationship between primary and university education with sexual function score (p<0. 343 and p<0.894, respectively). Conclusion: Based on the finding of this study, some factors, such as urinary incontinence, vaginal dryness, and hot flush were associated with lower sexual function scores and prolapse was correlated with a higher score of sexual function. There was no significant correlation between sexual function and education level.